2006
DOI: 10.1128/jvi.00013-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Cytoplasmic Tail of Jaagsiekte Sheep Retrovirus Envelope Protein

Abstract: Jaagsiekte sheep retrovirus (JSRV) is the etiologic agent of a transmissible lung cancer in sheep, ovine pulmonary adenocarcinoma. JSRV is unique in that the envelope protein functions as an oncogene, since it can morphologically transform fibroblast and epithelial cells in culture and can induce lung tumors in mice. Previous studies indicated that the transmembrane (TM) protein is essential for transformation, and particular attention has focused on a YXXM motif in the cytoplasmic tail. In this study, we carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 26 publications
7
44
0
Order By: Relevance
“…Based on transformed morphology, the transformation observed by Liu and Miller was higher than that observed in this study, which employed HA-tagged Env. JSRV Env proteins containing C-terminal epitope tags have a lower efficiency of transformation than does wild-type Env (17,27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Based on transformed morphology, the transformation observed by Liu and Miller was higher than that observed in this study, which employed HA-tagged Env. JSRV Env proteins containing C-terminal epitope tags have a lower efficiency of transformation than does wild-type Env (17,27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations of the YXXM motif of the JSRV-env gene abolish cell transformation of NIH-3T3 [43,61] and rat 208F and RK3E cells [38]. Akt activation was observed in different cell lines transformed by JSRV (Fig.…”
Section: Mechanisms Of Oncogenesismentioning
confidence: 88%
“…Activation of this signalling cascade leads to translocation of MAPK into the nucleus, where they activate different transcription factors. The Ras-MEK-MAPK pathway is activated in JSRVtransformed NIH 3T3 and RK3E cells [38,46] (Fig. 3).…”
Section: Mechanisms Of Oncogenesismentioning
confidence: 96%
See 1 more Smart Citation
“…Results from the previous experiment suggested that the LTRs are not entirely responsible for the cell-type-specific oncogenicity observed in naturally infected sheep and that perhaps other regions of the ovine betaretroviral genome contribute to the disease spectrum. The genomic sequences of JSRV and ENTV differ at the 3Ј end of the env gene, just upstream of the 3Ј LTR (29), in a region that has been shown to be dispensable for transformation (17), but possesses enhancer functions in other retroviruses (3,18). To test the potential role of this region in determining disease tropism, we incorporated the ϳ75-bp sequence upstream of the JSRV and ENTV-1 3Ј LTRs into AJAP and AE 1 AP to create A JE JAP and A EE E 1 AP, where JE stands for JSRV element and EE stands for ENTV element (Fig.…”
Section: Resultsmentioning
confidence: 99%